Association of the apparent diffusion coefficient with maturity in adolescent sacroiliac joints. Issue 3 (21st February 2016) - Bray, Timothy J.P.; Vendhan, Kanimozhi; Roberts, James; Atkinson, David; Punwani, Shonit; Sen, Debajit; Ioannou, Yiannis; Hall‐Craggs, Margaret A.
Abstract : Purpose: To determine the extent to which apparent diffusion coefficient (ADC) values vary with skeletal maturity in adolescent joints. Materials and Methods: A retrospective study was performed with Institutional Review Board (IRB) approval. We used a picture archiving and communication system (PACS) search to identify and recruit all adolescents who had undergone 1.5T magnetic resonance imaging (MRI) of the sacroiliac joints (SIJs) between January 2010 and June 2015, and had no evidence of sacroiliitis and normal inflammatory markers. In all, 55 individuals were assessed. For each patient, coronal and sagittal images of the sacrum were visually analyzed to determine sacral maturity. Patients were divided into three groups depending on the degree of fusion of the sacral segmental apophyses: "Fused, " "Partial, " and "Unfused." For each group, SIJ ADC was measured using a linear region‐of‐interest technique. Results: Mean ADC values were 690 × 10 −6 mm 2 /s in the fused group, 720 × 10 −6 mm 2 /s in the partial group, and 842 × 10 −6 mm 2 /s in the unfused group. ADC values were significantly higher in the unfused group than in the fused group ( P = 0.046). ADC values were also higher in unfused subjects than partially fused subjects ( P = 0.074). Conclusion: Joint ADC values are higher in skeletally immature (unfused) patients than in skeletally more mature (fused) patients. ADC values measured in the unfused group overlap with those previously reported in sacroiliitis. These results suggest that ADC measurements in adolescent joints must be interpreted in light of joint maturity. Joint immaturity may lead to misdiagnosis of sacroiliitis, since immature juxta‐articular bone may appear similar to inflammation. J. Magn. Reson. Imaging 2016. J. Magn. Reson. Imaging 2016;44:556–564.